BILABIAL FRICATIVE VOICELESS - VOICED SOUND BARRIER FOR SUNDANESSE SPEAKERS: A PEDAGOGICAL APPROACH - Yusuf, Teddy; Syhabbuddin, Syhabbuddin (Indonesian Journal of Learning and Instruction, 2024)
There are different educational institutions covering English as a foreign language in the country. In big cities, English is even taught in kindergarten, either because learning English is prestigious or because of school competition. Learning English was not a serious difficulty for some students of foreign languages, like the European states. But in Asia, that's not always the case — especially for those who speak a Polynesian language, and especially for the Sundanese. This is especially true for bilabial consonant sounds, which Sundanese speakers have difficulties pronouncing. These pronunciation variations are perfectly normal, because every language has its own sound inventory.Without a doubt, Sundanese and English differ markedly in their segmental phonology. Using two different languages in the same article for pedagogic purposes teaching English to a Sundanese speaker, this article is going to state the differences and similarities between the two. The contrastive analysis will highlight the differences and similarities between the two languages which will help language teachers and learners to overcome problems facing them in pronouncing English sounds.This study will investigate the differences and similarities between the consonant pronunciations in the two languages, with an emphasis on bilabials. The methodology used in this research is descriptive-qualitative. Using the approach of contrastive analysis, different similarities and differences of influence with the two languages are detailed, especially in bilabial consonant pronunciation. Due to language-specific differences between bilabial sounds, it is hoped that the findings would be a useful reference for language teachers and learners to prepare for targeted training or therapy. And the researcher hopes this study may assist language teachers for other languages, as well as speakers of Mandarin Chinese or similar languages, to overcome the production of bilabial sounds in English.Keywords: Contrastive Analysis; Inventory, Consonant; Sound Segment.